Grey matter myelination. Issue 11 (12th March 2019) - Timmler, Sebastian; Simons, Mikael
Abstract : There is now increasing evidence that myelin is not only generated early in development, but also during adulthood possibly contributing to lifelong plasticity of the brain. In particular, human cortical areas responsible for the highest cognitive functions seem to require decades until they have reached their maximal amount of myelination. Currently, we know very little about the mechanisms and the functions of grey matter myelination. In this emerging field key questions await to be addressed: How long does myelination last in humans? How is grey matter myelination regulated? What is the function of myelin in the grey matter? Does grey matter myelination limit and/or promote neuronal plasticity? Finding answers to these questions will be important for our understanding of normal, but also abnormal cortex function in a number of neurological and psychiatric diseases. Main points: Cortical areas responsible for the highest cognitive function contain less myelin. Grey matter myelin may generate oscillating neuronal networks. Grey matter myelin could function as an inhibitor of neuronal circuit plasticity.